2022
DOI: 10.3390/toxins14050349
|View full text |Cite
|
Sign up to set email alerts
|

Variation of Microbial Community and Fermentation Quality in Corn Silage Treated with Lactic Acid Bacteria and Artemisia argyi during Aerobic Exposure

Abstract: Silage, especially whole crop corn silage (WCCS), is an important part of ruminant diets, with its high moisture content and rich nutrient content, which can easily cause contamination by mold and their toxins, posing a great threat to ruminant production, food safety and human health. The objective of this study was to examine effects of lactic acid bacteria (LAB) Lactiplantibacillus (L.) plantarum subsp. plantarum ZA3 and Artemisia argyi (AA) on the fermentation characteristics, microbial community and mycot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 64 publications
3
11
0
Order By: Relevance
“…Contents of acetic acid in all AA-treated groups were significantly higher after ensiling 60 days. For appropriate acetic acid concentration that could inhibit yeast and improve aerobic stability, AA groups could significantly inhibit fungi and improve aerobic stability of silage, which were also consistent with the findings of Ma et al (2022) and Wang et al (2022b) .…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Contents of acetic acid in all AA-treated groups were significantly higher after ensiling 60 days. For appropriate acetic acid concentration that could inhibit yeast and improve aerobic stability, AA groups could significantly inhibit fungi and improve aerobic stability of silage, which were also consistent with the findings of Ma et al (2022) and Wang et al (2022b) .…”
Section: Discussionsupporting
confidence: 85%
“…At 2 and 4 days, the number of microorganisms in LB, 20% AA and AA groups were relatively high, and the compositions of microbial community in LB and 20% AA were gradually similar. This might because microbialcommunities in silage treated with LAB and AA changed along with environment from anaerobic to aerobic ( Wang et al, 2022b ).…”
Section: Discussionmentioning
confidence: 99%
“…The fungal richness decreased during aerobic exposure, in accordance with the ndings of previous research [35]. High fungal diversity can improve the aerobic stability of whole-plant corn silage [40]. In the present study, the fungal diversity showed no difference between treatments or between days of aerobic exposure (P > 0.05), indicating that the CTs did not prolong the aerobic stability of sainfoin silage.…”
Section: Fungal Communitysupporting
confidence: 91%
“…The contents of ammonia-N in all groups increased with prolonged aerobic exposure. This result is probably due to protein hydrolysis, which is typically caused by extensive protease ( Wang et al, 2022 ). Higher contents of ammonia-N and lower CP were observed in the BS group than in the other groups, illustrating that amino acid deamination was relatively active in BS silages.…”
Section: Discussionmentioning
confidence: 99%